2020
DOI: 10.3390/ma13122763
|View full text |Cite
|
Sign up to set email alerts
|

Preparation and Characterization of Defective TiO2. The Effect of the Reaction Environment on Titanium Vacancies Formation

Abstract: Among various methods of improving visible light activity of titanium(IV) oxide, the formation of defects and vacancies (both oxygen and titanium) in the crystal structure of TiO2 is an easy and relatively cheap alternative to improve the photocatalytic activity. In the presented work, visible light active defective TiO2 was obtained by the hydrothermal reaction in the presence of three different oxidizing agents: HIO3, H2O2, and HNO3. Further study on the effect of used oxidant and calcination temperature on … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
2
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 18 publications
(3 citation statements)
references
References 73 publications
0
2
0
Order By: Relevance
“…As mentioned in the Introduction, contrary results on the defective/hydrogenated/self-doped titania have been published, showing both activity increase and decrease under UV irradiation. For example, Bielan et al observed a decrease in activity for phenol degradation [67], whereas Zywitzki et al reported an activity enhancement for hydrogen evolution [68]. It has been proposed that Ti 3+ species might also reduce protons to H 2 or platinum cations (Pt 2+ ) to form Pt nanoparticles (NPs).…”
Section: Resultsmentioning
confidence: 99%
“…As mentioned in the Introduction, contrary results on the defective/hydrogenated/self-doped titania have been published, showing both activity increase and decrease under UV irradiation. For example, Bielan et al observed a decrease in activity for phenol degradation [67], whereas Zywitzki et al reported an activity enhancement for hydrogen evolution [68]. It has been proposed that Ti 3+ species might also reduce protons to H 2 or platinum cations (Pt 2+ ) to form Pt nanoparticles (NPs).…”
Section: Resultsmentioning
confidence: 99%
“…Titanium dioxide is a kind of semiconductor material with three crystal forms of anatase, rutile and brookite. Titanium dioxide has the characteristics of stable chemical properties, non-toxic, strong light stability, high oxidation efficiency and environmental friendliness [4][5][6][7] . However, in the practical application of photocatalysis technology, different materials and different preparation methods have certain effects on their photocatalytic properties, such as their composition, morphology, structure and other physical properties, thus affecting their chemical properties.…”
Section: Introductionmentioning
confidence: 99%
“…Thus far, many studies have been performed to investigate the stability of TiO 2 nanofluids with different concentrations and under various pH and ionic strength conditions [ 20 , 25 , 26 , 27 , 28 , 29 , 30 ]. The final objective of such research works is to define the best conditions for optimal performance of TiO 2 -based composites, whatever the field of application.…”
Section: Introductionmentioning
confidence: 99%